Surviving amidst barriers: Community based organizations and rural farmers' access to informal credit in Southeast Nigeria. Issue 2 (3rd July 2022) - Onyishi, Charity N.; Igbo, Emmanuel U.M.; Uwakwe, Emmanuel E.
ABSTRACT: In most developing countries, access to and use of financial services is low especially among rural farmers. These farmers face numerous difficulties in accessing formal credits. Due to limited access to formal credit, rural farmers are increasingly resorting to sourcing informal credits from community-based organizations (CBOs). Using qualitative data drawn from 24 in-depth interviews with officials of CBOs and nine focus group discussion sessions with experienced rural farmers, we examined how CBOs operate as savings and credit organizations, the impacts of the informal credits provided by the CBOs on rural farmers and the challenges of CBOs. The study revealed that CBOs are increasingly becoming a major provider of credit facilities to rural farmers in Southeast Nigeria. Through investments, savings and credit activities, the CBOs increase their capitals and make them available for loan. Our findings are useful for evidence-informed policy decisions.